The internet of things and the protection of human rights: ethical and legal challenges - Horielova, V.Yu.; Горєлова, Вероніка Юріївна (Таврійський національний університет імені В.І. Вернадського, 2025)
The article examines the topical issue of ethics and law of the Internet of Things (IoT), since today, thanks to the improvement of sensor technologies, wireless communication and data processing, IoT has evolved from a concept to an integral element of modernity, transforming almost all spheres of human existence (economy, transport, healthcare and other areas, ensuring process automation, resource optimisation and development of smart systems). The article outlines the ethical aspects of using IoT, in particular, those related to transparency, fairness of algorithms and respect for human rights. It is noted that IoT stimulates the progress of artificial intelligence, while massive data collection and storage create risks of violation of human privacy, which requires strict legal regulation. Thus, the issue of ‘algorithm ethics’ becomes an urgent one, as algorithm-based solutions can be biased, which requires transparency and human responsibility for technology development. The successful development of IoT requires a combination of legal regulation, technical measures, international standards and educational programmes to ensure a safe and fair digital environment. The article presents a list of problems associated with the practical application of the Internet of Things. The author emphasises the need to develop and implement ethical standards for the Internet of Things (IoT), which is an important means of ensuring security and protecting human privacy in the technological environment. The article also discusses existing international ethical standards for the Internet of Things, including the principles of data protection, security, transparency and responsibility. These principles promote the integration of ethics into the technology development process, ensuring that IoT not only performs technical functions but also complies with ethical standards, in particular in terms of protecting human privacy
Інтернет речей і захист прав людини: етичні та правові виклики
Keywords: Internet of Things; human rights; ethics; privacy; data protection; cybersecurity; artificial intelligence; digital governance; algorithmic transparency; legal regulation